2008
DOI: 10.1002/da.20271
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of duloxetine in the treatment of generalized anxiety disorder: a flexible-dose, progressive-titration, placebo-controlled trial

Abstract: Generalized anxiety disorder (GAD), a prevalent and chronic illness, is associated with dysregulation in both serotonergic and noradrenergic neurotransmission. Our study examined the efficacy, safety, and tolerability of duloxetine hydrochloride, a dual reuptake inhibitor of serotonin and norepinephrine, for short-term treatment of adults with GAD. In a 10-week, double-blind, progressive-titration, flexible-dose trial, 327 adult outpatients with a DSM-IV-defined GAD diagnosis were randomized to duloxetine 60-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
96
2
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(105 citation statements)
references
References 24 publications
(19 reference statements)
5
96
2
2
Order By: Relevance
“…48 These doses may be useful in depression or anxiety, for example with 18.28% patients taking 120 mg/day in a general anxiety disorder study with flexible dosing. 49 In cases of efficacious dosing, in agreement with the presented studies, it is possible to stop duloxetine after 3 to 6 months, and eventually 12 months. 33 After this period of remission, the dose may be gradually decreased, with regular assessments.…”
Section: Patient Preference and Recommended Management Of Duloxetine:supporting
confidence: 80%
“…48 These doses may be useful in depression or anxiety, for example with 18.28% patients taking 120 mg/day in a general anxiety disorder study with flexible dosing. 49 In cases of efficacious dosing, in agreement with the presented studies, it is possible to stop duloxetine after 3 to 6 months, and eventually 12 months. 33 After this period of remission, the dose may be gradually decreased, with regular assessments.…”
Section: Patient Preference and Recommended Management Of Duloxetine:supporting
confidence: 80%
“…There were 22 double-blind RCT (online suppl. As for duloxetine, 1 study [8] reported a significantly greater incidence of discontinuation-emergent adverse events (DEAE) in duloxetine-treated patients compared to placebo, whereas 2 trials did not [9,10].…”
Section: Resultsmentioning
confidence: 99%
“…In the RCT that reported data about the comparison between SNRI and placebo, withdrawal symptoms were significantly higher after discontinuation of venlafaxine [11,12,19,22] and desvenlafaxine [15,16,23,34], whereas they did not differ from placebo in most of the trials on duloxetine [9,10,17,22,[24][25][26]33] or in the studies on levomilnacipran [14] and milnacipran [13]. The duration of treatment with venlafaxine or desvenlafaxine was as short as 2 months [11,15,16,23].…”
Section: Discussionmentioning
confidence: 99%
“…In one of these studies, venlafaxine was superior to placebo, whereas in the second trial the difference to placebo could not be demonstrated on the primary efficacy measure, but only on some secondary outcome measures (A). Á Duloxetine was more effective than placebo in DBPC studies (Koponen et al 2007;Rynn et al 2007aRynn et al , 2008. Also, in three-arm studies, both duloxetine and the comparator venlafaxine were better than placebo (Hartford et al 2007;Nicolini et al 2008).…”
Section: Generalized Anxiety Disorder (Gad)mentioning
confidence: 88%